Research on Dynamic Characteristics of the Engine Front-end Accessory Drive System - Zheng Guangze; Yan Pengyuan; Wu Yu; Li Xiaofeng (Jixie chuandong)
Considering the effects of time-varying load, time-varying excitation, longitudinal stiffness, radial stiffness and bending stiffness of each pulley, the dynamic analysis model of the inner and outer engine front-end accessory drive system is established by Simdrive software. The static characteristics of the system are evaluated. Galerkin method is used to discretize the system space, the implicit multi-step method is used to solve the dynamic characteristics of the system under acceleration conditions, and the influencing factors of the accessory pulley speed fluctuation, tension fluctuation and belt-pulley slip characteristics are obtained. Based on the analysis results, an improvement plan is proposed to appropriately increase the initial tension and the crankshaft wheel wrap angle, and add an automatic tensioner at the No.2 idler gear. The comparison analysis shows that the dynamic characteristics of the engine front-end accessory drive system are improved effectively when adding automatic tensioner.